Functional Traits of the World's Late Quaternary Terrestrial Mammalian Predators - Eamonn I. F. Wooster; Erick J. Lundgren; Mairin Balisi; Rhys T. Lemoine; Christopher J. Sandom; Jens‐Christian Svenning; John Rowan; Chris J. Jolly; Grant D. Linley; Mitchell. A. Cowan; Nick Wright; Dylan Westaway; et al. (Global Ecology and Biogeography, 2024)
Motivation Terrestrial predators play key roles in cycling nutrients, as well as limiting prey populations, and shaping the behaviour of their prey. Prehistoric, historic and ongoing declines of the world's predators have reshaped terrestrial ecosystems and are a topic of conservation concern. However, the availability of ecologically relevant predator functional traits is limited, hampering efforts to understand macroecological changes in this ecologically important functional group. Here, we present CarniTraits , a comprehensive open‐access functional trait database of all late Quaternary (~130,000 ybp) terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Main Types of Variables Contained Mammalian terrestrial predator functional traits including body mass, diet, scavenging, locomotion, cooperative hunting, hunting habitat, hunting method, bone consumption, temporal activity patterns, brain mass and encephalisation quotient. Spatial Location and Grain Global. Time Period and Grain Late Quaternary (the last ~130,000 years). Major Taxa and Level of Measurement All late Quaternary terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Software Format csv.